A comparison of two methods for acquiring ecological data on armadillos from Argentinean Pampas: field work versus interviews - Abba, Agustin Manuel (2010)
The objective of this work is to compare information collected on the ecology of three species of Pampean armadillos (Chaetophractus villosus, C. vellerosus and Dasypus hybridus), obtained through interviews with the information obtained previously in a typical ecological field study. The study area encompasses ~1000km2 of the northeastern part of the Pampas grasslands of Argentina. Thirty four farms evenly distributed throughout the study area were randomly selected and either the farmer or an employee was interviewed on the presence of armadillos. Traditional ecological data were collected in two ways: searching for indirect signs of armadillos and capturing and marking live individuals. The majority of the results were coincident between both methods. It is concluded that interviews can contribute to ecological research in the Pampas grassland by helping to design field surveys in the initial phase of a study. Interviews can be an important tool in decision making regarding land use and management, because they are a low cost method in terms of time and budget, and do provide reliable results.